2020
DOI: 10.1371/journal.pgen.1008642
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape of undifferentiated embryonal sarcoma of the liver is typified by C19MC structural rearrangement and overexpression combined with TP53 mutation or loss

Abstract: Undifferentiated embryonal sarcoma of the liver (UESL) is a rare and aggressive malignancy. Though the molecular underpinnings of this cancer have been largely unexplored, recurrent chromosomal breakpoints affecting a noncoding region on chr19q13, which includes the chromosome 19 microRNA cluster (C19MC), have been reported in several cases. We performed comprehensive molecular profiling on samples from 14 patients diagnosed with UESL. Congruent with prior reports, we identified structural variants in chr19q13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…C19MC is a cluster of 46 miRNAs located at chr19q13.42 16 , 17 . C19MC miRNAs have been implicated in multiple cancer types such as breast cancer 17 , embryonal tumors with multilayered rosettes (ETMRs) 18 , infantile hemangioma 19 , thyroid adenomas 20 , testicular germ cell tumors 21 , parathyroid tumors 22 , undifferentiated embryonal sarcoma of the liver (UESL) 23 , including hepatocellular carcinoma 24 26 . However, the role of C19MC miRNAs in the context of MYO18B gene transcription is not known to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C19MC is a cluster of 46 miRNAs located at chr19q13.42 16 , 17 . C19MC miRNAs have been implicated in multiple cancer types such as breast cancer 17 , embryonal tumors with multilayered rosettes (ETMRs) 18 , infantile hemangioma 19 , thyroid adenomas 20 , testicular germ cell tumors 21 , parathyroid tumors 22 , undifferentiated embryonal sarcoma of the liver (UESL) 23 , including hepatocellular carcinoma 24 26 . However, the role of C19MC miRNAs in the context of MYO18B gene transcription is not known to date.…”
Section: Introductionmentioning
confidence: 99%
“…tumors 22 , undifferentiated embryonal sarcoma of the liver (UESL) 23 , including hepatocellular carcinoma [24][25][26] . However, the role of C19MC miRNAs in the context of MYO18B gene transcription is not known to date.…”
mentioning
confidence: 99%
“…Accordingly, a loss of genomic imprinting has been reported in a wide range of tumors, such as Wilms’ tumors, lung carcinomas, neuroblastomas, acute myeloblastic leukemias, rhabdomyosarcomas, and sporadic osteosarcomas [ 21 ]. In fact, many imprinted genes tend to be organized in large clusters (e.g., IGF2-H19, DLK1-DIO3 or C19MC), suggesting the potential involvement of higher order regulatory elements for these regions [ 14 , 22 , 23 , 24 , 25 , 26 , 27 ]. A better-characterized imprinted cluster in cancer is the chromosome 11p15.5 region.…”
Section: Discussionmentioning
confidence: 99%
“…Case studies and series have identified mutations in the DNA-binding domain of the TP53 gene [ 161 , 172 ] as well as somatic mutations in WDR25, CMTM1, and DNHA17 [ 173 ], although these are reported in single cases and further investigation into the exact pathogenesis is required [ 30 ]. Whole exome sequencing was performed in a sample of 14 patients with UESL, which found that the combination of C19MC hyperexpression via chromosomal structural event with TP53 mutation or loss was a highly recurrent genomic feature of UESL [ 171 ].…”
Section: Malignant Tumors In School-aged Children and Adolescentsmentioning
confidence: 99%